How Far Is the Future? - Pinkus , Karen (img journal, 2020)
The pandemic and consequent economic fallout, intertwined with the climate crisis, has led to a recalibration of the distance that separates the present from the future. This essay draws on media theory to delineate some of the paradoxes involved in predicted or knowing when the future will have arrived during this period of ‘new normal’.